Anatomical investigations in Silybum marianum (L.) Gaertn - Sidhu MC; P, Saini (Journal of Research in Biology, 2011)
Anatomical studies have been carried out for various parts of species Silybum marianum (L.) Gaertn. According to the available literature very little work has been done on this aspect. Keeping this in view presently, the root, stem and leaf of this plant has been studied in detail for its anatomical variations. Stem anatomy is almost similar to other members of the family. The Transverse Section of the leaf shows the presence of accessory vascular bundles. Similarly Transverse Section of the root has revealed the occurrence of secondary growth. In normal conditions, secondary growth if occur, has to be present in other plant parts also e.g., stem. But it has not been observed in stem during present investigation. Further, stomata have not been found on any of the two epidermal layers. In addition, to best of our knowledge, no anatomical details has been worked out for this species in the past except one study made on root anatomy as discussed in the results. So present findings related to the anatomy of this particular species may be treated as pioneer.